Changes in depressive symptoms over age among older Americans: Differences by gender, race/ethnicity, education, and birth cohort - Leah R. Abrams; Neil K. Mehta (Elsevier, 2019)
Despite concerns about recent trends in the health and functioning of older Americans, little is known about dynamics of depression among recent cohorts of U.S. older adults and how these dynamics differ across sociodemographic groups. This study examined sociodemographic differences in mid- and late-life depressive symptoms over age, as well as changes over time. Using nationally representative data from the Health and Retirement Study (1994-2014), we estimated mixed effects models to generate depressive symptoms over age by gender, race/ethnicity, education, and birth cohort in 33,280 adults ages 51-90 years. Depressive symptoms were measured using the 8-item Center for Epidemiological Studies Depression scale. Women compared to men, low compared to high education groups, and racial/ethnic minorities compared to whites exhibited higher depressive symptoms. The largest disparity resulted from education, with those without high school degrees exhibiting over two more predicted depressive symptoms in midlife compared to those with college degrees. Importantly, war babies and baby boomers (born 1942-1959) exhibited slightly higher depressive symptoms with more decreasing symptoms over age than their predecessors (born 1931-1941) at ages 51-65. We additionally observed an age-as-leveler pattern by gender, whereby females compared to males had higher depressive symptomology from ages 51-85, but not at ages 86-90. Our findings have implication for gauging the aging population's overall well-being, for public health policies aimed at reducing health disparities, and for anticipating demand on an array of health and social services.